Infrastructure Anthropology: Inequality of Access and Mobility - Djufri (Indonesian Journal Publisher, 2025)
Infrastructure development is often positioned as a symbol of urban progress, but in practice, it often creates inequality of access and mobility, especially for marginalized groups. This research aims to examine how infrastructure is produced, interpreted, and contested in the daily lives of suburban urban communities in Makassar. With a critical ethnography approach, data was collected through participatory observation, in-depth interviews, and field documentation, and then analyzed using the theory of spatial production (Lefebvre), dispossession (Harvey), habitus and social capital (Bourdieu), and Actor-Network Theory (Latour). The results of the study show that infrastructure in Makassar is not neutral, but rather an exclusive space that strengthens social inequality. Societies exhibit various forms of symbolic resistance—from replenishment of empty spaces to cultural adaptation to new systems. These findings show that space is a field of contention that continues to be produced and negotiated. This research emphasizes the importance of building inclusive and participatory infrastructure, by making citizens not just development objects, but active actors in the formation of urban space.